(untitled) (Nexo Revista Científica, 2022)
The paper presents research into the effects of macro-roughness on the leading edge of the plate imitating excrescences on the fins of humpback whales on the value of hydrodynamic losses. The authors compare calculations with experimental results obtained on a hydrodynamic flume. All studies are performed using the Ansys CFX and Autodesk CFD computer simulation packages. Based on the obtained findings, the authors make conclusions on the feasibility of applying macro-roughening on the leading edge of the plate. The conducted computational and experimental research demonstrates the positive effects of a certain configuration of spherical macro-roughness on the hydrodynamic characteristics of the plate in the case of spillage in an open-type hydrodynamic flume.